Rational design of semiconductor crystal for efficient photocatalytic chemical conversion - Bu, Jing (2016)
Semiconductor based energy conversion from solar energy to chemical energy is one of the most possible solution for the severe worldwide energy crisis and followed environmental issues. However due to the low efficiency, the commercial application of semiconductor based energy conversion is still limited and further modification for better performance is required. Hence this thesis tries to improve the photocatalytic property of semiconductor by several kinds of modifications including control synthesis of TiO2 with 3D hierarchical structure, loaded Pt nanoclusters with discrete energy levels and combination of TiO2 and Cu2O with different exposed crystal planes. Nano-flower like rutile TiO2 hierarchical structures have been synthesized by a solvent-thermal method. The structure of the nano-flowers was carefully characterized via various techniques, such as XRD, Raman spectra, UV-Vis diffuse reflectance spectra, XPS et al. we found that the building blocks of such nano-flower structures are single-crystalline rutile TiO2 nanorods with their growth along [001] axis and exposed (110) facet on nanarods’ side walls. Owing to this hierarchical nanostructure, this rutile TiO2 showed enhanced photocatalytic activity for the selective oxidation from Benzylamine to N-BIBL. This suggests the great potential of this 3D highly ordered hierarchical structure in many other photocatalytic applications, such as PEC or DSSCs. It is well accepted that Pt is the best cocatalyst for photocatalytic H2 generation from water splitting. However, most consumed Pt is nanoparticles but not Pt nanoclusters with discrete energy levels which show totally different properties due to quantum size effect. In this thesis Pt nanoclusters protected by L-glutathione reduced (GSH) are deposited on the surface of anatase TiO2 with enhanced photocatalytic activity and stability. It is suggested that the synergistic effect of TiO2 and Pt nanoclusters is crucial for the improved photocatalytic performance. And the size of prepared Pt nanoclusters shows great influence on the photocatalytic performance. Pt nanoclusters open a door for better modification of TiO2 by tuning property of co-catalyst atom by atom. Besides the controlled modification to obtain fancy morphology of TiO2 or decorated TiO2 with suitable cocatalysts, facet controlled combination of TiO2 with other semiconductor (Cu2O) is achieved. TiO2 is successfully deposited on the surface of Cu2O with different morphologies which exposed different crystal planes. The combination enhances the photocatalytic activity of the nanocomposites and improves the stability of the TiO2 hybrid Cu2O photocatalysts. In conclusion, we developed different modification strategies for pristine TiO2 to obtain improved photocatalytic activity. These researches on the modification strategies and their positive influence on the photocatalytic performance of the modified TiO2 based photocatalysts suggests the rational design for the nano-structures of these catalysts is very crucial for the acquisition of desired catalytic properties of these catalysts. And this thesis show the promising prospect of the rational designed complex ordered nanostructures and their diverse applications in photocatalysis.